Synovial Chondromatosis of Shoulder Treated by Arthroscopic Synovectomy and Removal of Loose Bodies: A Case Report - Thapa, Sushil; Pant, Sunil; Dhakal, Prasesh (Nepal Orthopaedic Association Journal, 2023)
Synovial Chondromatosis of the shoulder is mentioned in literature as a rare case. It is a benign neoplastic condition of the synovial membrane. Multiple osteocartilaginous loose bodies inside the joint characterize this rare monoarticular disorder. This case report describes a 32-year-old man who presented with right shoulder pain for six months. He had painful abduction and internal rotation. The condition was diagnosed as synovial chondromatosis. The patient underwent arthroscopic removal of loose bodies and synovectomy. This case illustrates the investigation and treatment of synovial chondromatosis of the shoulder. The loose bodies in synovial chondromatosis of a shoulder joint can be retrieved by arthroscopy as it provides a broader field of vision, better accessible access to the loose bodies, synovectomy, reduced hospital stay, and better rehabilitation.